(untitled) (Ghana Journal of Science, Technology and Development, 2022)
Landuse and landcover have over the decades been undergoing changes as a result of natural and human activities. These changes for a given area can be attributed to fluctuations in the infiltration ability of the land, leading to changes in the hydrological cycle of a given catchment area. This research assessed some of the impacts that landuse and landcover changes coupled with climate variations have on the hydrological components of the Oti sub-basin of Ghana using the Soil Water Assessment Tool (SWAT) with ArcGISÂ® interface for the development of models from which conclusions were drawn. The research incorporated into the SWAT system two landuse and landcover data: 1984 and 2013 which were modeled and evaluated alongside soil, slope and climate dataset. The results from running the model indicated a very significant change in landuse and landcover and a loss of forest cover which has negative effect on the hydrological components of the basin. Also, the rainfall trend analysis gave negative significant values of -2.28 and -2.78 for the two stations located at Zabzugu and Bimbila within the basin. Together, these changes have led to an increase in evapotranspiration (ET) and decrease in surface water, lateral ï¬‚ow and groundwater recharge. This is an indication that climate change impact on the basin is a function of the landuse and landcover changes. There is an urgent need for all stakeholders to help protect the basin from anthropogenic activities such as farming too close to the basin in order to prevent future water availability issues in the basin.